2021
DOI: 10.1055/s-0041-1728803
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Repair of the Dorsal Intercarpal Ligament Detachment from the Scaphoid

Abstract: Background The dorsal intercarpal ligament, whose role in dorsal stability of the wrist has been shown, can be harmed in case of injury to the dorsal scapholunate complex. However, dorsal intercarpal ligament injury also seems to exist isolated posttraumatic forms of dorsal intercarpal ligament rupture, much rarer, through bony avulsion on its scaphoid insertion. The authors report the first description of this lesion, and propose a technique for arthroscopic repair. Description of Technique Radiocar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…7 Merlini and Mathoulin reported an arthroscopical repair of a detachment of the DICL on the scaphoid side. 8 Our arthroscopical reinforcement suture can be performed when persistent radioscaphoid instability is coexisting with the RSCL still present but insufficient due to elongation. The procedure does not require tendon grafts, bone tunnels or anchors and causes potentially less fibrosis and stiffness than open reconstructions.…”
Section: Discussionmentioning
confidence: 99%
“…7 Merlini and Mathoulin reported an arthroscopical repair of a detachment of the DICL on the scaphoid side. 8 Our arthroscopical reinforcement suture can be performed when persistent radioscaphoid instability is coexisting with the RSCL still present but insufficient due to elongation. The procedure does not require tendon grafts, bone tunnels or anchors and causes potentially less fibrosis and stiffness than open reconstructions.…”
Section: Discussionmentioning
confidence: 99%
“…Isolated DICL tears are uncommon, at least in the published literature. 17 It is often associated with intrinsic intercarpal ligament (SLIL and LTIL) and extrinsic ligament injuries (volar radiocarpal or DRCLs) such as those seen in perilunate injuries or midcarpal instability. 28 29 The lack of data on isolated DICL tears is likely due to the lack of knowledge of such pathology, leading to missed diagnosis and delayed presentation.…”
Section: Discussionmentioning
confidence: 99%
“…We performed the procedure for arthroscopic repair of DICL avulsion as described by Merlini and Mathoulin. 17 After RCJ exploration through the 3–4 portal using a standard wrist arthroscopy setup, the camera is switched to the 6-R portal, leaving the 1–2 and 3–4 portals as the working portals for instrumentation and repair. One can visualize the avulsed DICL from the scaphoid ridge through the 6-R portal ( Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since this technique has been described and perfected by Mathoulin, [2][3][4][5][6] we have operated on several hundred patients presenting with an acute or even chronic tear of the scapholunate interosseous ligament (SLIL). Previous published research has shown that at 4-year follow-up, the majority of patients had good to excellent Mayo Wrist Score.…”
mentioning
confidence: 99%